Pathological analysis of cystic lesions of the bones: a retrospective single-center 10-year overview - Özgün, Gonca; Yalçınkaya, Ulviye; Yazıcı, Zeynep; Sarısözen, Bartu (The European Research Journal, 2018)
Objective: Many different neoplastic and non-neoplastic lesions involve the skeletal system. Clinical and radiological tools primarily assess the nature of these lesions.The aim of this study was to analyze the cystic bone lesions in a pathologic point of view.Methods: All bone cysts between 2002 and 2013 retrospectively evaluated under the guidance of clinical information and radiological images. Descriptive data such as age, gender, tumor site, symptoms, and clinical and radiological findings obtained from the hospital’s database system. Results: There were 96 cystic bone lesions; 47 were aneurysmal bone cysts (ABCs), 37 were simple bone cysts (SBCs), one was a lesion with features of both ABC and SBC, four were intraosseous ganglia, four were epidermoid cysts, and three were hydatid cysts. The mean ages of the patients with ABCs and SBCs were 18.7 ± 12.8 years (range, 3-75 years) and 23.8 ± 13.3 years (range, 3-62 years), respectively. Most of the lesions located in the long bones.Conclusions: Cystic lesions of the bone rarely encountered in daily pathology routine. As with all conditions affecting the skeletal system, one of the most important steps towards an accurate pathological diagnosis is to perform with clinical and radiological information while evaluating the patients.